2022
DOI: 10.5812/ijpr-123825
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Different Radioiodine Doses for Post-ablation Therapy of Thyroid Remnants: A Systematic Review

Abstract: : The determination of radioiodine remnant ablation (RRA) dosage in post-operation thyroid residual tissues resection has been largely subject of discussion, yet no concise conclusion is released through systematic review studies. In this study, we conducted a systematic review of comparative experiments to evaluate and compare the efficacy of different prescribed dosages of radioiodine in post-op thyroid residual tissues resection among low, intermediate, and high-risk patients to approve the common method. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In certain past studies, the therapeutic efficacy of intermediaterisk DTC patients treated with higher doses of RAI therapy (3.7GBq or 5.55GBq) has not been found to be superior to those treated with lower doses (1.11GBq or 3.7GBq) (17)(18)(19)(20)(21). Moreover, 3.7GBq RAI therapy is often associated with a higher frequency of short-term adverse effects compared to 1.11GBq or 1.875GBq (17,20,21). Nevertheless, another report indicated that 5.55GBq RAI is associated with a lower recurrence rate than 3.7 GBq RAI for high-risk DTC patients (22).…”
Section: Discussionmentioning
confidence: 98%
“…In certain past studies, the therapeutic efficacy of intermediaterisk DTC patients treated with higher doses of RAI therapy (3.7GBq or 5.55GBq) has not been found to be superior to those treated with lower doses (1.11GBq or 3.7GBq) (17)(18)(19)(20)(21). Moreover, 3.7GBq RAI therapy is often associated with a higher frequency of short-term adverse effects compared to 1.11GBq or 1.875GBq (17,20,21). Nevertheless, another report indicated that 5.55GBq RAI is associated with a lower recurrence rate than 3.7 GBq RAI for high-risk DTC patients (22).…”
Section: Discussionmentioning
confidence: 98%
“…The unstimulated thyroglobulin level may still be detectable in roughly 50% of patients with a full response on imaging. Thyroglobulin levels are frequently low, steady, or even declining without further therapy (4) . The majority of facilities use a fixed dose of radioiodine treatments.…”
Section: Introductionmentioning
confidence: 99%